Molecular investigation of Toxocara infection from the serum of people living with HIV in Alborz, Iran - Mohammad Zibaei; Zahra Hatami; Farzaneh Firoozeh; Fatemeh Bakhshipour; Abolfazl Miahipour; Alireza Soleimani; Elham Shokri (BMC Infectious Diseases, 2023)
Abstract Background Toxocara infection is one of the most common neglected infections of poverty and a helminthiasis of global importance. Traditional diagnostic methods such as antibodies detection in serum samples are limited due to cross-reactivity and poor sensitivity. The use of molecular base methods for diagnosis of Toxocara infection in Iran has not been fully explored. The purpose of the current study was to estimate the prevalence of Toxocara infection from serum samples of people living with HIV in Alborz province, Iran using serological and molecular methods. Methods Blood samples were collected from 105 people living with HIV. Epidemiological data of participant were obtained through a structured questionnaire to investigate the risk factors. Patients CD4+ T cell count were recorded. Anti-Toxocara IgG antibodies were detected by ELISA, with a cut-off point of 11. PCR was performed to detect genetic material of Toxocara species in the serum samples. Results The mean CD4+ count in HIV-infected individuals with positive toxocariasis serology was 255.1 ± 21.6 cells/µL. Seropositivity for Toxocara species was observed in 12/105 (11.4%) people living with HIV. Three samples gave positive results on PCR analysis. Based on the data, a statistically significant relationship was found between anti-Toxocara IgG antibodies seropositivity and underlying conditions (p = 0.017). No significant statistical association was observed between seropositivity for Toxocara and gender, age, exposure to domestic animals or pet keeping, education levels, and occupation (p > 0.05). The findings of PCR confirmed Toxocara DNA in 3/12 (25.0%) serum samples. Conclusion These findings demonstrated for the first time that people living with HIV from Alborz province, are being exposed to this zoonosis and a relatively high seroprevalence of Toxocara in HIV/AIDS people needs comprehensive health education regarding personal hygiene and how to avoid exposure to this parasite infection, especially in people with an impaired immune system.